AN ANALYSIS OF ENGLISH NATIONAL EXAM AND ENGLISH TEACHERS’ PERCEPTION USING BLOOM’S REVISED TAXONOMY - Andreas Lalogiroth; Devilito P. Tatipang (English Education Department, 2020)
This study was conducted in the purpose of revealing the cognitive domains of Bloom’s Revised Taxonomy in 2015/2016 English National Exam for senior high school level and also finding out English teachers’ perception on the result of 2015/2016 English National Exam questions for senior high school level. Furthermore, this study is classified as a descriptive study, for it analyzed questions used in National Exam and this did not deal with numerical data. The research investigated the cognitive domain used in the National Exam’s questions based on the revised form of Bloom Taxonomy. In addition, quantitative method, in this research, was used to support the qualitative one. This is to know the percentage of using cognitive domains in the questions. This also aims at deciding the most frequent or dominant level applied in the questions in accordance with Bloom’s Revised Taxonomy. Three versions of 2015/2016 English National Exam for senior high school level were chosen from three different programs in senior high school, natural science program, social science program and language program. From each program, the researcher took one version. Then, the questions were grouped based on Bloom’s Revised Taxonomy using checklist as instrument. In obtaining qualitative data, the researcher conducted a semi-structured interview and three schools were chosen in Tondano. There were six teachers to be interviewed. The finding shows that the cognitive domains of Bloom’s Revised Taxonomy used in question items of 2015/2016 English National Exam for senior high school level are remembering, understanding, applying and analyzing levels.